Alleviation of liver fibrosis by inhibiting a non-canonical ATF4-regulated enhancer program in hepatic stellate cells - Li-Xian Yang; Chuangye Qi; Si Lu; Xiang-Shi Ye; Parnaz Merikhian; Du-Yu Zhang; Tao Yao; Jiang-Sha Zhao; Ying Wu; Yongshi Jia; Bo Shan; Jinghai Chen; et al. (Nature Communications)
Abstract Liver fibrosis is a critical liver disease that can progress to more severe manifestations, such as cirrhosis, yet no effective targeted therapies are available. Here, we identify that ATF4, a master transcription factor in ER stress response, promotes liver fibrosis by facilitating a stress response-independent epigenetic program in hepatic stellate cells (HSCs). Unlike its canonical role in regulating UPR genes during ER stress, ATF4 activates epithelial-mesenchymal transition (EMT) gene transcription under fibrogenic conditions. HSC-specific depletion of ATF4 suppresses liver fibrosis in vivo. Mechanistically, TGFβ resets ATF4 to orchestrate a unique enhancer program for the transcriptional activation of pro-fibrotic EMT genes. Analysis of human data confirms a strong correlation between HSC ATF4 expression and liver fibrosis progression. Importantly, a small molecule inhibitor targeting ATF4 translation effectively mitigates liver fibrosis. Together, our findings identify a mechanism promoting liver fibrosis and reveal new opportunities for treating this otherwise non-targetable disease.